Numerical Solution for Complex Systems of Fractional Order - Rabha W. Ibrahim (Journal of Applied Mathematics)
By using a complex transform, we impose a system of fractional order in the sense of Riemann-Liouville fractional operators. The analytic solution for this system is discussed. Here, we introduce a method of homotopy perturbation to obtain the approximate solutions. Moreover, applications are illustrated.